Twilight : Volume 1 / the graphic novel. - Kim, Young, (Illustrator); Meyer, Stephenie, 1973- (New York : Yen Press, 2010)
When seventeen-year-old Bella leaves Phoenix to live with her father in Forks, Washington, she meets an exquisitely handsome boy at school for whom she feels an overwhelming attraction and who she comes to realize is not wholly human.
Keywords: Meyer, Stephenie, -- 1973- -- Adaptations; Vampires -- Fiction; High schools -- Fiction; Schools -- Fiction; Washington (State) -- Fiction; Graphic novels